Non-fungible token: Overview and use cases - Carolin Diefenbach (RheinMain University of Applied Sciences, Wiesbaden Institute of Finance and Insurance (wifin), 2023)
Due to the rapid growth experienced by the market for non-fungible tokens in 2021, the topic has become much more present. Even people who have not previously dealt with the topic of cryptoassets are finding interest in it. What exactly is hidden behind the term NFT, which areas of application there are and in which direction crypto tokens are developing will be briefly presented in this article. Significant changes on the market and in the technological field will be highlighted, as well as opportunities and challenges. – – Aufgrund des rasanten Wachstums, das der Markt für Non-fungible Token im Jahr 2021 erfahren hat, ist das Thema deutlich präsenter geworden. Auch Personen, die sich zuvor nicht mit dem Thema Kryptoassets auseinandergesetzt haben, finden Interesse daran. Was genau sich hinter dem Begriff NFT verbirgt, welche Einsatzgebiete es gibt und in welche Richtung sich die Kryptotoken entwickeln, soll in diesem Artikel kurz dargestellt werden. Dabei werden signifikante Veränderungen am Markt und im technologischen Bereich beleuchtet sowie Chancen und Herausforderungen.
Keywords: 650; crypto-assets; virtual assets; non-fungible token; smart contracts; blockchain; proof of work; proof of stake